Bi12O17Cl2 with a Sextuple BiO Layer Composed of Rock‐Salt and Fluorite Units and its Structural Conversion through Fluorination to Enhance Photocatalytic Activity. (2nd August 2022) - Kato, Daichi; Tomita, Osamu; Nelson, Ryky; Kirsanova, Maria A.; Dronskowski, Richard; Suzuki, Hajime; Zhong, Chengchao; Tassel, Cédric; Ishida, Kohdai; Matsuzaki, Yosuke; Brown, Craig M.; Fujita, Koji; et al.
Abstract: Layered bismuth oxyhalides with bilayered (Bi2 O2 ) fluorite (FL) slabs are promising visible‐light photocatalysts because of their excellent stability and the ability to adjust band levels depending on the layers combined. It is interesting to manipulate the Bi2 O2 slab itself, but only trilayered FL blocks (e.g., Bi3 O4 ) are reported so far. Here, a structurally uncharacterized Bi12 O17 Cl2, which is extensively studied as a photocatalyst for a variety of reactions, has a sextuple Bi6 O8.5 block separated by Cl is shown. Unlike double and triple layered cases, the inner region of the Bi6 O8.5 block contains 1D rock‐salt (RS) units in the FL matrix along the a ‐axis, causing in‐plane corrugation. A topochemical reaction involving anion‐exchange gives Bi12 O17–0.5 x F x Cl2 ( x  ≤ 6) with alternate FL and RS slabs along the c ‐axis. The elimination of the structural corrugation increases higher photo‐conductivity and improves photocatalytic activity against acetic acid decomposition under visible light irradiation. This study paves new opportunities of controlling the properties of layered bismuth oxyhalides by the thickness of Bi–O block, FL/RS configuration, and structural modulation. Abstract : Bi12 O17 Cl2, whose structure is unknown but widely studied as a photocatalyst, is found to have a layered structure with corrugated sextuple Bi6 O8.5 layer separated by chloride anions. Topochemical fluorination removes the modulation of the sextuple block and enhances the photocatalytic activities.